2021
DOI: 10.3390/ma14030563
|View full text |Cite
|
Sign up to set email alerts
|

Research on the Properties of Mineral–Cement Emulsion Mixtures Using Recycled Road Pavement Materials

Abstract: The reduction in natural resources and aspects of environmental protection necessitate alternative uses of waste materials in the area of construction. Recycling is also observed in road construction where mineral–cement emulsion (MCE) mixtures are applied. The MCE mix is a conglomerate that can be used to make the base layer in road pavement structures. MCE mixes contain reclaimed asphalt from old, degraded road surfaces, aggregate improving the gradation, asphalt emulsion, and cement as a binder. The use of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 60 publications
0
6
0
Order By: Relevance
“…These challenges arise not only from externally imposed regulations encouraging the shift towards a "green" economy but also by economic benefits and incentives of low-emission technologies. These conditions require the introduction of new, energy-efficient techniques incorporating new types of materials, such as reclaimed materials [1][2][3][4][5][6][7], reinforcement [8][9][10][11], and producing asphalt mixtures at decreased temperatures [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…These challenges arise not only from externally imposed regulations encouraging the shift towards a "green" economy but also by economic benefits and incentives of low-emission technologies. These conditions require the introduction of new, energy-efficient techniques incorporating new types of materials, such as reclaimed materials [1][2][3][4][5][6][7], reinforcement [8][9][10][11], and producing asphalt mixtures at decreased temperatures [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…The reduction in natural resources and aspects of environmental protection necessitate alternative uses for waste materials in the area of construction [ 51 ]. Recycling is also observed in road construction, where mineral–cement emulsion (MCE) mixtures are applied.…”
Section: Description Of the Articles Presented In The Issuementioning
confidence: 99%
“…It was found that it was possible to reduce the stiffness and cracking in MCE mixes. The use of innovative binders will positively affect the durability of road pavements [ 51 ].…”
Section: Description Of the Articles Presented In The Issuementioning
confidence: 99%
“…The properties of mixtures containing RAP with virgin aggregate and cement-emulsion mortar are known for practical use as mineral-cement-emulsion mixtures (MCEM). In Poland, first requirements were published in 1999 by IBDiM Issue 61 [ 3 ], since then many years of laboratory and field research [ 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 ] also FWD measurements of pavement after 13 years of using [ 12 ] have been made. The disadvantages of MCEM base courses in Poland include mainly: transverse cracks, accelerated degradation in the weakest places of the layer where fatigue damage has reached the value of D = 50%, the commonly used “in situ” method that does not ensure uniformity of the layer made [ 12 ].…”
Section: Introductionmentioning
confidence: 99%